Hand hygiene adherence in intensive care units: comparison before and during the COVID-19 pandemic in a municipality of São Paulo state - Vanessa Aparecida Vilas-Boas; Pedro Antonio Teodoro de Moraes; Marcela Grispino Vieira Torres de Lolo; Edinêis de Brito Guirardello; Maria Isabel Pedreira de Freitas (Einstein (São Paulo))
ABSTRACT Objective: Compare alcohol-based hand sanitizer use in intensive care units in a municipality in São Paulo state, before and during the coronavirus pandemic. Methods: Analytical retrospective study using indirect documentation, with data obtained from a notification spreadsheet for epidemiological indicators of healthcare-associated infection in the state. Data on monthly alcohol-based sanitizer use were collected from the intensive care units of public and private general hospitals of the municipality. Analysis was conducted using descriptive statistics and graphically with run charts. The Mann-Whitney test was applied to compare the median consumption of public and private hospitals, at a 5% significance level. Results: Adult, neonatal and pediatric intensive care units showed median increases in hand sanitizer use of 34.03 to 57.64, 31.53 to 48.66 and 34.38 to 60.35mL/patient-day, respectively. Private hospitals showed greater hand sanitizer use in the adult and pediatric intensive care units compared to public institutions. Conclusion: The pandemic contributed to increasing hand sanitizer use in municipal intensive care units, but there is still room for improvement. More effort is needed to ensure that hand sanitizer use remains high.